Currents in the Historical Linguistics and Linguistic Dating of the Hebrew Bible: Report on the State of Research as Reflected in Recent Major Publications - Rezetko, Robert (HIPHIL Novum, 2019)
In this essay we summarize the status quaestionis of diachronic linguistic study of Biblical Hebrew as reflected principally in some major publications of the recent several years. We reflect critically on research objectives, perspectives on sources, documentation of variation and change, and periodization issues. We also include a detailed bibliography of relevant works published since our Historical Linguistics and Biblical Hebrew (November 2014).